2018
DOI: 10.1093/ejcts/ezy029
|View full text |Cite
|
Sign up to set email alerts
|

Bioprosthetic mitral valve replacement in patients aged 65 years or younger: long-term outcomes with the Carpentier–Edwards PERIMOUNT pericardial valve†

Abstract: In the selected patients aged 65 years or younger undergoing mitral valve replacement with a pericardial bioprosthesis, the expected valve durability was 14.2 years. Reoperation for SVD was associated with a low risk of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 25 publications
4
19
1
1
Order By: Relevance
“…Hence, they can show a slightly higher average age [ 10 , 14 ] . Studies carried out on samples with rheumatic being the most prevalent etiology show lower averages, as well as that found in the present study [ 16 , 17 ] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Hence, they can show a slightly higher average age [ 10 , 14 ] . Studies carried out on samples with rheumatic being the most prevalent etiology show lower averages, as well as that found in the present study [ 16 , 17 ] .…”
Section: Discussionsupporting
confidence: 88%
“…The Global Rheumatic Heart Disease Registry, or the REMEDY study [ 2 ] , and Remenyi, ElGuindy, Smith, Yacoub, and Holmes [ 4 ] also showed a predominance of this sex among the total affected by rheumatic disease, whether in developed countries or not. Most studies on mitral surgery have a mostly female population [ 10 - 17 ] .…”
Section: Discussionmentioning
confidence: 99%
“…If uncontrolled, SVD critically impairs the functioning of the implanted valve, causing recurrent stenosis or insufficiency [ 6 , 7 , 8 ]. In spite of the current advances in the design and manufacturing of BHVs, SVD remains a common long-term complication [ 9 , 10 , 11 ] demanding a repeated valve replacement in half of the patients 15 years post-implantation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because patients with rheumatic heart disease are relatively young, the main feature of the group is younger patients underwent MVR. Moreover, 84.86% of the patients were classified as NYHA class III or above, and 19.37% were diagnosed as NYHA class IV before valve replacement, suggesting a worse preoperative cardiac condition in Chinese patients than in European and American patients (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Even considering the level of healthcare service, the severity of patient condition at first visit, patient awareness of self-care, and economic conditions in China, survival analysis showed that the 10-year survival rate is satisfied compared to its foreign counterparts on average, especial in AVR and DVR (12)(13)(14)(15). The more comparable result is from Chinese local patients replaced with Perimount bovine pericardial bioprosthetic valves (14).…”
Section: Discussionmentioning
confidence: 99%